(untitled) (Global Journal of Human-Social Science, 2021)
The conduct of regular elections by authoritarian populist regimes has engendered the advent of elections without democracies and democracies without rights and peoples participation The unwillingness of the elites and the powerful who have taken hold of the political system to cede to the views of the people is increasingly making the government unresponsive The political system is fast turning into a playground for billionaires with very high propensity to exclude the people from the scheme of affairs Political parties are getting frozen by populist leaders who are using their positions to destroy free media undermine independent institutions and muzzle the opposition Individual and minority rights as well as popular will are no longer guaranteed Citizens are thus disillusioned with politics have grown restless angry disdainful and hostile to the resultant democrazy This paper therefore analyzed the collapsing party prowess in membership and candidate recruitments that have pushed politicians on self-worth electioneering political merchandising and entrepreneurship in their search for relevance It further examines the vertical linkages between political parties and electorates as complemented by horizontal connection between parties and private contributors